What is the impact of blood pressure on neurological symptoms and the risk of ESKD in primary and secondary thrombotic microangiopathies based on clinical presentation: a retrospective study - Jean-Michel Halimi; Benjamin Thoreau; Florent von Tokarski; Adeline Bauvois; Juliette Gueguen; Nicolas Goin; Christelle Barbet; Sylvie Cloarec; Elodie Mérieau; Sébastien Lachot; Denis Garot; Adrien Lemaignen; et al. (BMC Nephrology, 2022)
Abstract Background The impact of blood pressure on neurological symptoms and risk of end-stage kidney disease (ESKD) is unknown in primary and secondary thrombotic microangiopathies (TMAs). Methods We measured baseline systolic (SBP) and diastolic (DBP) BP in consecutive 563 patients with adjudicated primary and secondary TMAs, and assessed its association with the risk of ESKD. Results Normal BP, grade 1, 2 and 3 hypertension were present in 243 (43.1%), 132 (23.4%), 101 (17.9%) and 88 (15.6%), respectively. Significant BP differences were noted in relation to the cause of TMA: highest BP values were found in patients with atypical hemolytic-uremic syndrome (aHUS), pregnancy, transplantation and auto-immune-related TMAs. Normal BP or grade 1 hypertension was found in 17/18 (94.4%) patients with thrombotic thrombocytopenic patients (only 1/18 (5.6%) had a SBP value>150 mmHg). In contrast, BP values could not differentiate isolated “essential” malignant hypertension (MH) from MH associated with aHUS (isolated MH (n=15): BP (median (IQR)): 220 (182-249)/132 (101-150) mmHg; MH with aHUS (n=5): BP: 223 (196-245)/131 (111-144) mmHg). The risk of vigilance disturbances (6.9%, 15.0%, 25.0%, respectively), epileptic seizures (1.5%, 4.0%, 12.5%, respectively) and posterior reversible encephalopathy syndrome (0.76%, 2.97%, 6.82%, respectively) increased with increasing baseline BP values from grade 1 to grade 3 hypertension. ESKD occurred in 35/563 (6.2%) patients (1.23%, 2.27%, 11.9% and 19.3% of patients with normal BP, grade 1, 2 and 3 hypertension, respectively). As compared to patients with normal BP (<120/139 mmHg), grade 1, grade 2 and grade 3 hypertension were associated with a greater risk of ESKD in univariate (OR: 1.91 [0.83-4.40], 13.2 [3.56-48.9] and 34.8 [9.31-130], respectively) and multivariate (OR: 0.89 [0.30-2.69], 7.00 [1.57-31.3] and 19.7 [4.53-85.2], respectively) analyses. The association between BP and the risk of ESRD was unchanged after adjustment on eculizumab use (OR: 3.46 [1.41-8.49], 17.7 [4.44-70.0] and 70.6 [8.61-579], respectively). Patients with MH, regardless of its cause, had a greater risk of ESKD (OR: 26.4 [10.0-69.8] vs other patients). Conclusions Baseline BP differs in primary and secondary TMAs. High BP reduces the neurological tolerance of TMAs and is a powerful independent risk factor of ESKD, even after adjustment on TMA’s cause.